The Controlled Synthesis of Birnessite Nanoflowers via H2O2 Reducing KMnO4 For Efficient Adsorption and Photooxidation Activity - Li, Yang; Jiang, Guanjie; Ouyang, Nanqi; Qin, Zhangjie; Lan, Shuai; Zhang, Qin (Frontiers in Chemistry, 2021)
Birnessite nanoflowers composed of layers has been proven to be the strongest adsorbent and oxidant in the surface environment. However, the current synthesis method of birnessite nanoflowers were suffering from long reaction time and high reaction temperature. Based on these, this paper explores a new method for the rapid and controlled synthesis of layered manganese oxides. The method relies on variations in the molar ratios of KMnO4 and H2O2 redox reacting species to drive the production of birnessite nanoflowers under acidic conditions. The molar ratios of KMnO4 and H2O2 is the key to the crystal structure of the as-prepared. It was found that when the molar ratios of KMnO4 and H2O2 is from 1:1.25 to 1:1.90, the sample is birnessite nanoflowers, and when the ratio is increased to 1:2.0, the sample is a mixture of birnessite nanoflowers and feitknechtite nanoplates. Among the as-prepared samples, BF-1.85 (molar ratios of KMnO4 and H2O2 is 1:1.85) shows the highest capacity for Pb2+ adsorption (2955 mmol/kg) and greatest degradation efficiency of phenol and TOC. The method proposed herein is economical and controllable, and it yields products with high efficiency for the elimination of inorganic and organic pollutants.